Optimizing Institutional Identity: A Strategic Approach through Religious Culture in Higher Education - Permanasari, Engelien Yusniar; Soebiantoro, Soebiantoro; Haryanti, Nik (JURNAL AL-TANZIM, 2023)
This research aims to determine strategies for strengthening higher education identity through religious culture at UNISBA Blitar. This research uses a descriptive qualitative approach. The data was collected using purposive sampling through interviews, observation and documentation. After the data was obtained, the researcher analyzed the data by carrying out data condensation, display, and concluding. The research results show that the strategy to strengthen the identity of higher education at UNISBA Blitar is carried out by first requiring all students to take Islamic religious education courses and certification to instil Islamic values (the dimensions of creed) in students. Second, the policy is to take the Al-Qur'an Reading Test (TBQ) and tahsinul Qur'an guidance to improve students' reading and understanding of the Islamic holy book (shari'ah dimension). Third, the policy of dressing/dressing in sharia when on campus is to foster student politeness and neatness (moral dimension). Creating student religious culture uses a structural model (top-down). The fundamentals that must be upheld in strengthening religious culture in higher education are as follows: congregational prayer movement, Islamic dress movement, thaharah movement, exemplary movement, Islamic hospitality movement, and quality of life movement.